Uso de rotíferos Brachionus quadridentatus y nauplios de artemia en la alimentación de post larvas de gamitana Colossoma macropomum (Cuvier, 1816). - Gómez Ríos, Karen Gissell (2023)
In fish farming the critical stage is the post-larval stage and is influenced by the type of food offered in the first feeding. The present research work was carried out within the facilities of the Peruvian Amazon Research Institute (IIAP) located on the Iquitos-Nauta highway km 4.5 during the months of February and March of the year 2022. The objective was to evaluate the effect of the feeding of post larvae of the gamitana Colossoma macropomum with rotifers, brine shrimp nauplii and their combinations in the productive performance, survival and water quality of the post larvae of Colossoma macropomum, in 4 feeding treatments: (Brine brine shrimp; Rotifer - Brachionus quadridentatus; Rotifer + Artemia Nauplius; Rotifer (05 to 06 dpe) and Artemia Nauplii (07 to 16 dpe)). The density of rotifers was 5 rot/ml in each treatment and for nauplii it was 20% of the weight of the post-larvae. The feeding frequency was 5 times a day until 16 dpe. 24,000 larvae 1 day post-hatching (dpe) were used and distributed in 16 30 L tanks (50 larvae/L) in a constant recirculation system. The results show that at 09 dpe and 16 dpe the postlarvae that had brine shrimp nauplii in their diet achieved better percentages in survival and productive performance with a significant difference with the treatment of only Rotifers. In conclusion, diets containing brine shrimp nauplii achieved optimal results, probably due to better nutritional quality compared to the rotifer-only diet.